A plastic surgery education: Malaysian emergency burn management (MEBM) course / Shah Jumaat Mohd Yussof ... [et al.] - Mohd Yussof, Shah Jumaat; Miswan, Akmal Hisham; Md Mydin Siddik, Nur Shazwani Farah; Ilenghoven, Devananthan; Ibrahim, Salina (Universiti Teknologi MARA, Perak, 2020)
Burn injuries are among the most common trauma in the world. Alarmingly, our previous study discovered that 55% of the first responders that treat burns had difficulty in managing burns in the emergency setting. To improve the delivery of emergency burn care, we designed a course that provides burn-specific trauma management guidelines called the Malaysian Emergency Burns Management (MEBM) course. We aim to provide sufficient factual and clinical information to enable front medical liners to deal competently with burn emergencies. This course was written and designed by our team and received endorsements from two Malaysian medical societies. The first MEBM course was conducted from 24th till 25th April 2019, in conjunction with the 3rd International Burn & Wound Conference 2019, in Kelantan. We had a sold-out event with encouraging feedback from the participants. We have also received recognition from the Malaysian Society for Care of Trauma (MASCOT) in the form of an invitation to run the second MEBM course during their annual Malaysia Trauma Conference. The faculty of Medicine has approved the second MEBM course and the organizing work is underway. Thereon we plan to register this course as an annual event in the medical calendar year.